THE EVALUATION OF HIGH PROTEIN FOOD PROCESSING AS NUGGET IN PEKON TANJUNG JATI TANGGAMUS DISTRICT - Susanti Susanti; Zukryandry Zukryandry; Hertini Rani (Indonesian Journal of Community Empowerment (IJCE), 2020)
The trend consumption foods of ready to cook and ready to eat is an alternative choice for the community and increasing public awareness about nutrition and health encourages people to live healthier lives by consuming nutritious foods and have a healthy effect. Processing nuggets production of the Tanjung Jati Women's Farmers Group is quite well received by consumers but the processing of this product is still done with simple technology. Improvements or technological touches need to be done so that the resulting nugget products have added value. The current problem causes the economic benefits that should have been obtained from this production activity can not be felt optimally. Community service is carried out in Tanjung Jati Pekon, Kota Agung Timur District, Tanggamus Regency. Activities in the form of counseling, socialization and practice of nugget product processing and packaging techniques are located at the Balai Rakyat Pekon Tanjung Jati, Kota Agung Timur District, Tanggamus District and the time to carry out activities in January 2020. The nugget training procedures include: a preliminary survey, counseling for the development of nugget product processing for Wanita Tani Pekom Tanjung Jati, socialization of the regulations of the head of the Indonesian drug and food regulatory body regarding packaging and labeling, technical guidance on processing and packaging of nuggets, and technical guidance on business plans and marketing of nuggets. The results of the activities showed the average value of the initial and final evaluation scores of the trainees was 34.77 and 82.50. If viewed from the increase in the score, it appears that an increase in score of 47.8 points. This shows that the training activities went quite well. The training activities were able to motivate the Tanjung Jati Pekon Women Farmers Group in Tanggamus Regency to develop the region's businesses. Advice from the training activities of making and packaging nuggets require further assistance to develop various local resource-based businesses